Environmental and Social Policy and Procedures : Volume 1. Mizoram - World Bank (Washington, DC, 2015)
The prime objective of the project/subproject is to improve the power sector in the State of Mizoram and capacity building to achieve sustainable development in the long term. The Project is expected to facilitate connection to remote/virgin area, to enhance the capacity & reliability of the system, to improve voltage profile & to reduce losses and ultimately to enhance satisfaction for all categories of consumers which in turn will spur growth & overall development in the whole State.